2016
DOI: 10.1016/j.adolescence.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of adolescent substance use development and the influence of healthy leisure: A growth mixture modeling approach

Abstract: Considerable heterogeneity exists in adolescent substance use development. To most effectively prevent use, distinct trajectories of use must be identified as well as differential associations with predictors of use, such as leisure experience. The current study used a person-centered approach to identify distinct substance use trajectories and how leisure is associated with trajectory classes. Data came from a larger efficacy trial of 2.249 South African high school students who reported substance use at any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…Adding a PROM to assess family functioning will need to be mindful of this complexity. PROMs to assess whether SUD treatment facilitated engagement in recreational alternatives face a similar challenge given limited availability of these activities in many South African communities and affordability and accessibility barriers to participation [33,34]. Despite these measurement challenges, our findings that adolescents think that these factors matter for their SUD treatment outcomes, confirm that adult-oriented PROMs for SUD treatment need to be adapted for greater relevance to adolescents.…”
Section: Discussionmentioning
confidence: 57%
“…Adding a PROM to assess family functioning will need to be mindful of this complexity. PROMs to assess whether SUD treatment facilitated engagement in recreational alternatives face a similar challenge given limited availability of these activities in many South African communities and affordability and accessibility barriers to participation [33,34]. Despite these measurement challenges, our findings that adolescents think that these factors matter for their SUD treatment outcomes, confirm that adult-oriented PROMs for SUD treatment need to be adapted for greater relevance to adolescents.…”
Section: Discussionmentioning
confidence: 57%
“…In their research, Chiapetti et al concluded that one of the reasons for drug abuse was its fun [55]. Weybright also referred to the protective role of leisure activities against drug abuse [56].…”
Section: Discussionmentioning
confidence: 99%
“…Designated Q statements were provided to address the raised issues related to drug use prevention during supervisory interactions. The statement sentences were developed according to a literature review [ 6 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] and experiences of youth counsellors. The research team discussed the draft statements with two senior youth counsellors; both worked with students of drug use problem for more than 10 years.…”
Section: Methodsmentioning
confidence: 99%
“…The research team discussed the draft statements with two senior youth counsellors; both worked with students of drug use problem for more than 10 years. After several group discussions, the statements were categorized as follows: strengthen information with personal relevance [ 6 , 36 , 37 , 38 ], health consequences of drug use [ 30 , 32 , 33 ], overcome barriers to change [ 6 , 28 , 33 , 34 , 35 ], development of preventive strategies [ 35 , 36 , 37 , 38 ], and supportive relationships [ 29 , 35 , 39 ]. The statements were later reviewed by three health professionals with expertise on drug use to ensure their appropriateness.…”
Section: Methodsmentioning
confidence: 99%